How do the neurocognitive profiles of FASD and complex trauma compare in the pediatric population?: A scoping review protocol - Rishi Gupta; Colleen Pawliuk; Denise Somuah-Asamoah; Katelynn E. Boerner; Jennifer Engle; Sarah Hutchison; Gurpreet K. Salh (PLoS ONE, 2025)
Objective The aim of this scoping review is to compare the neurocognitive profiles of children and youth diagnosed with Fetal Alcohol Spectrum Disorder (FASD) to those of children and youth diagnosed with complex trauma. Introduction The neurocognitive challenges resulting from prenatal alcohol exposure (PAE) have been defined by the FASD diagnosis. Complex trauma exposure, in the form of adverse childhood experiences (ACEs), is associated with similar neurocognitive deficits. Recent evidence suggests ACE exposures to be higher in individuals with FASD as compared to non-FASD controls which warrants a closer look at the overlap between the neurocognitive deficits associated with FASD and complex trauma. A more robust understanding comparing the neurocognitive profiles of FASD and complex trauma can guide assessment, diagnosis, and interventions to support the long-term management of youth with cognitive impairments. Inclusion criteria The review will assess various studies that evaluate the neurocognitive profiles of FASD and complex trauma amongst the pediatric population (aged 0–18). Complex trauma will be defined as multiple interpersonal traumatic events that happen in childhood. The context of this review is pediatric patients diagnosed with FASD or exposed to complex trauma. Methods We will search MEDLINE (Ovid), Embase (Ovid), PsycINFO (EBSCO), Scopus and Google Scholar. Additionally, will conduct backwards and forwards citation searching of all included sources. Title and abstract screening and full-text review will be performed by at least two independent reviewers. Data extraction will be performed using a tool developed for this review. The results will be presented in a narrative and tabular format.